STEM Education as a Concept Borrowing Issue: Perspectives of School Administrators in Turkey. (February 2023) - Kulakoglu, Busra; Kondakci, Yasar
Purpose: As a borrowed concept, science, technology, engineering, and mathematics (STEM) education holds limited relevance in many country contexts. This study investigates how school administrators in Turkey view STEM education from three dimensions: (a) their understanding of STEM education, (b) their experiences of STEM implementations, and (c) their perception of their roles in STEM implementation. Design/Approach/Methods: This phenomenological study analyzes the perceptions of school principals working in prominent high schools in Turkey. Findings: The findings indicate that there are gaps in STEM implementation at both the conceptual level and the school level, including epistemological issues, infrastructural gaps, mismatch with overall organizational culture, and knowledge and skill gaps. Despite efforts to integrate STEM education into educational practices, significant deficiencies are making it an unrealistic practice in Turkey. Originality/Value: While the literature on STEM education is expanding, a few empirical studies focus on school management in relation to STEM education. Arguably, despite promising to transform science and mathematics teaching, STEM education appears to have limited relevance to science and mathematics teaching in Turkey—rendering it yet another example of concept and policy borrowing in education.